GAYA HIDUP, LITERASI KEUANGAN DAN PENGELOLAAN KEUANGAN MAHASISWA - Mutiya Oktariani; Acep Fatchuroji; Damayanti Damayanti (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This study aims to analyze the influence of financial literacy and lifestyle on the financial management of university students in Merauke. The research background highlights the relatively low level of financial literacy among students, which often leads to consumptive behavior, including the unplanned use of online loans. This research employed a quantitative approach with purposive sampling, involving 100 students from various universities in Merauke who were enrolled in introductory accounting or financial management courses. Data were collected using a questionnaire that had been tested for validity and reliability, and then analyzed using multiple linear regressions. The findings reveal that financial literacy has a positive and significant effect on students’ financial management, while a consumptive lifestyle has a negative and significant effect. Demographic factors such as gender, year of study, and university of origin show no significant influence. These results emphasize the importance of improving students’ financial literacy through educational programs, seminars, and non-formal activities so that they can manage their finances wisely, reduce consumptive behavior, and prepare for financial independence in the future. However, this study is limited by its restricted scope, as the respondents consist solely of students in Merauke.